Фармакоэпидемиология постинфарктного кардиосклероза и приверженноть больных лечению - О. Н. Курочкина; А. Л. Хохлов; Д. А. Копылова; Н. А. Швайко; А. Н. Богомолов (Архивъ внутренней медицины)
The investigation of prescribing to patients with myocardial infarction in the recommendations on discharge from hospital and outpatient was provided. Patients were studied by polling performance of medical prescriptions; found the average level of compliance. The reasons for low compliance were: forgetfulness, lack of pain, medication “on demand”, long term after myocardial infarction. The factors of compliance to treatment: female, recent months after a heart attack, the credibility to the doctor, a high level of medical and social awareness, the absence of bad habits.